FAKTOR-FAKTOR YANG MEMPENGARUHI PROFITABILITAS PADA SEKTOR PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE TAHUN 2014-2016 - YogiePrayogo, 12.05.52.0226; Badjuri, Achmad (Students' Journal of Accounting and Banking, 2019)
The purpose of this study is to examine and analyze the influence of the ratio of capital, asset quality and third party funds, BOPO and LDR to the profitability of banking companies in the Indonesia Stock Exchange in 2014-2016. The population of this study is that the population is banks that go public on the IDX in 2014-2016, the total sample of companies is 29 samples taken using the purposive sampling method. The type of data used is secondary data using documentation data collection methods. The analytical method in this study is multiple regression analysis.The results of this study indicate that Capital Adequacy Ratio (CAR) has a significant positive effect on profitability. Asset quality measured by PPAP has a significant negative effect on profitability. Third party funds have a significant positive effect on profitability. BOPO has a significant negative effect on profitability. Loan To Deposit (LDR) does not significantly influence profitability.